The Undergraduate Student’s Knowledge Towards Early Detection of Breast Cancer - Tiwale, Rupali; Mohite, Vaishali R.; Shinde, Mahadeo B (International Journal of Psychosocial Rehabilitation, 2020)
Introduction-: Among women, breast cancer is common cause of mortality, accounting for 16% of cancer deaths in adult women. Breast cancer is major life-threatening public health problem of great concern. Long-term increases in incidence of disease are being observed in both industrialized and developing world study was aimed to assess the undergraduate student’s knowledge towards early detection of breast cancer. Methods: cross-sectional study was conducted with 100 undergraduate nursing students. A self-structured questionnaire utilised, Data analysis was done using descriptive and inferential statistics. Results: As to information on hazard factors for breast malignant growth, (89%) realized that there are chance components associated with the improvement of breast disease. Concerning early breast cancer (45.2%) respondents for the most part referenced that it doesn’t cause torment and indication Regarding the phase of breast disease treatability (74%) react at phase of 0 and I followed by (20%) at stage 0, I and II and 15 (6%) concurred it isn’t reparable in any way. Respondents were asked to state the early detection measures for breast cancer; (75%) mentioned BSE, (45%) identified breast examination by a health professional (CBE), and only (39%) stated mammography as an early detection measures. Majority of the respondents (57 %) knew that breast cancer can be prevented at early stage of the disease; (33.0%) of them responded it can be prevented before the disease manifests, while (7.0%) said it cannot be prevented at all. Conclusion-In conclusion majority of undergraduate students were not knowledgeable regarding breast cancer and its screening technique. It is possible to recommend a need to improve breast cancer content in the higher secondary education curriculum; The media should let wide range of air time to provide comprehensive information about breast cancer as it can reach many people.